An Electrodeposited MXene‐Ti3C2Tx Nanosheets Functionalized by Task‐Specific Ionic Liquid for Simultaneous and Multiplexed Detection of Bladder Cancer Biomarkers. Issue 46 (8th October 2020) - Sharifuzzaman, Md.; Barman, Sharat Chandra; Zahed, Md. Abu; Sharma, Sudeep; Yoon, Hyosang; Nah, Joong San; Kim, Hyunsik; Park, Jae Yeong
Abstract: Controlled deposition of 2D multilayered nanomaterials onto different electrodes to design a highly sensitive biosensing platform utilizing their active inherent electrochemistry is extremely challenging. Herein, a green, facile, and cost‐effective one‐pot deposition mechanism of 2D MXene‐Ti3 C2 T x nanosheets (MXNSs) onto conductive electrodes within few minutes via electroplating (termed electroMXenition) is reported for the first time. The redox reaction in the colloidal MXNS solution under the effect of a constant applied potential generates an electric field, which drives the nanoparticles toward a specific electrode interface such that they are cathodically electroplated. A task‐specific ionic liquid, that is, 4‐amino‐1‐(4‐formyl‐benzyl) pyridinium bromide (AFBPB), is exploited as a multiplex host arena for the substantial immobilization of MXNSs and covalent binding of antibodies. A miniaturized, single‐masked gold dual interdigitated microelectrode (DIDμE) is microfabricated and presented by investigating the benefit of AFBPB coated on MXNSs. The resulting MXNSs‐AFBPB‐film‐modified DIDμE biosensor exhibited a 7× higher redox current than bare electrodes owing to the uniform deposition. Using Apo‐A1 and NMP 22 as model bladder cancer analytes, this newly developed dual immunosensor demonstrated precise and large linear ranges over five orders of significance with limit of detection values as low as 0.3 and 0.7 pg mL −1, respectively. Abstract : Successfully develop a green, facile, cost‐effective, and reliable deposition method of 2D MXNSs onto conductive electrodes within 3 min via electroplating technique (termed electroMXenition). Under constant potential, the redox reaction in the colloidal MXNS solution generates an electric field, which drives the nanoparticles toward a specific electrode interface such that they are cathodically electroplated to form crystalline MXNSs.